Alternative Trajectories for the Optimization of Trochoidal Milling in Hardened Steel - Kaciê K.A. Trindade; Josean da S. Lima Junior; Maxime Montoya; Alessandro R. Rodrigues; Kleber G.B. Alves; Flávio J. da Silva (Materials Research)
This study investigates the machining performance of trochoidal toolpaths in hardened AISI 4340 steel. Three toolpaths—conventional, horizontal semi-ellipse, and vertical semi-ellipse—were analyzed in terms of machining time and machining forces under dry and flood coolant conditions. Computer Numerical Control (CNC) programs were optimized using circular interpolation and repetition commands to minimize number of command blocks and maintain effective feed rates. Results showed the vertical semi-ellipse trajectory reduced machining time by 18.9% compared to the conventional path, while the horizontal semi-ellipse presented stable machining forces across both dry and wet conditions but had the longest machining time. The use of coolant significantly decreased machining forces in the conventional and vertical semi-ellipse trajectories, enhancing performance. The semi-ellipse paths demonstrated smoother tool transitions and optimized material removal, offering superior force stability. These findings underscore the importance of selecting toolpath geometry and cooling strategies to balance efficiency and stability in industrial machining applications.